Digital Health Innovations in Environmental Risk Monitoring: A Literature Review - Augustinus Robin Butarbutar; Jilly Toar; Priscilia Pingkan Mamuaja (Systematic Literature Review Journal, 2025)
Environmental health risks, including air pollution, unsafe water, and climate-sensitive diseases, remain pressing global challenges that continue to threaten public well-being. Conventional monitoring systems are typically manual, costly, and geographically limited, making it difficult to provide timely and accurate data for intervention. This study explores how digital health technologies—specifically mobile health (mHealth), the Internet of Things (IoT), artificial intelligence (AI), and remote sensing—are applied to strengthen the monitoring and management of environmental health risks. A structured literature review was carried out by synthesizing 87 peer-reviewed articles published between 2013 and 2024, using an evaluation framework built on keyword clustering, metadata filtering, and multi-criteria scoring to assess usability, scalability, interoperability, and relevance to health outcomes. Findings show that mHealth platforms are highly accessible and user-friendly but often face limitations in integration with broader health systems. IoT and AI technologies offer strong scalability and predictive capability, particularly in real-time risk detection, though they are hindered by interoperability issues across platforms. Meanwhile, remote sensing is powerful for capturing large-scale environmental data but lacks direct connections to health-specific applications. The analysis identifies a critical gap in the integration of these technologies, emphasizing the need for cross-sector collaboration to build more robust, interoperable systems. Additionally, the findings highlight the importance of ethical considerations, validation processes, and interdisciplinary approaches to ensure sustainable and impactful implementation. Overall, this study provides not only a comparative synthesis of current practices but also a methodological roadmap to guide future digital innovations in environmental health. By bridging technological potential with practical application, it underscores the urgent need for integrated strategies that can better address the growing complexity of environmental health risks in the modern era.